Availability and readiness of healthcare facilities and their effects on antenatal care services uptake in Bangladesh - Md. Nuruzzaman Khan; Md. Badsha Alam; Atika Rahman Chowdhury; Md. Awal Kabir; Md. Mostaured Ali Khan (BMC, 2024)
Abstract Background Sustainable Development Goal (SDG) 3.7 aims to ensure universal access to sexual and reproductive healthcare services, where antenatal care (ANC) is a core component. This study aimed to examine the influence of health facility availability and readiness on the uptake of four or more ANC visits in Bangladesh. Methods The 2017/18 Bangladesh Demographic and Health Survey data were linked with the 2017 Health Facility Survey and analyzed in this study. The associations of health facility-level factors with the recommended number of ANC uptakes were determined. A multilevel mixed-effect logistic regression model was used to determine the association, adjusting for potential confounders. Results Nearly 44% of mothers reported four or more ANC uptakes, with significant variations across several areas in Bangladesh. The average distance of mothers' homes from the nearest health facilities was 6.36 km, higher in Sylhet division (8.25 km) and lower in Dhaka division (4.45 km). The overall uptake of the recommended number of ANC visits was positively associated with higher scores for the management (adjusted odds ratio (aOR) 1.85; 95% CI, 1.16-2.82) and infrastructure (aOR, 1.59; 95% CI, 1.09-2.19) of health facilities closest to mothers' homes. The odds of using the recommended number of ANC in mothers increased by 3.02 (95% CI, 2.01-4.19) and 2.36 (95% CI, 2.09-3.16) folds for each unit increase in the availability and readiness scores to provide ANC services at the closest health facilities, respectively. Every kilometer increase in the average regional-level distance between mothers' homes and the nearest health facilities reduced the likelihood of receiving the recommended number of ANC visits by nearly 42% (aOR, 0.58, 95% CI, 0.42-0.74). Conclusion The availability of healthcare facilities close to residence, as well as their improved management, infrastructure, and readiness to provide ANC, plays a crucial role in increasing ANC services uptake. Policies and programs should prioritize increasing the availability, accessibility, and readiness of health facilities to provide ANC services.